Correction: Hartley et al. BVLOS Unmanned Aircraft Operations in Forest Environments. Drones 2022, 6, 167 - Hartley RJAL; Henderson IL; Jackson CL (MDPI (Basel, Switzerland), 2023)
In the original publication, there was a mistake in the legend for Table 1. There was an error in the original table calculations for “Approximate Square Area”. Now that they have been corrected, we would like to adjust the table caption to clarify to the readers how the calculations were made. The correct legend appears below. The authors state that the scientific conclusions are unaffected. This correction was approved by the Academic Editor. The original publication has also been updated. “Table 1. Approximate maximum operating areas based upon VLOS limitations, where VLOS range is equal to the distance between the centre and corner of the calculated square areas and the radius of the calculated circular areas.” In the original publication, there was a mistake in Table 1 as published. In the published table, the maximum operational area of a square flight plan was calculated incorrectly. The calculations were made using the maximum distance to calculate the distance from the centre of the square to the edge of the square rather than from the centre of the square to the corner of the square. The corrected Table 1 appears below. The authors apologize for any inconvenience caused and state that the scientific conclusions are unaffected. This correction was approved by the Academic Editor. The original publication has also been updated.